Betel Leaf Extract’s Effect (Piper Batle Linn) on The Healing Process of Incision Wounds in Rats (Rattus Norvegicus) - Suharto, Idola Perdana Sulistyoning; Ramayanti, Eva Dwi; Yunalia, Endang Mei; Ulfa, Novia (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
ABSTRACT.Introduction: An incision wound is a wound that is intentionally made by a clean-cut using a sharp object. Betel leaf is a natural ingredient that helps the wound healing process because it has active ingredients such as saponins, tannins, flavonoids, essential oils, and alkaloids. Objectives: The study aimed to determine the effect of betel leaf extract on the healing process of incision wounds in white rats. Methods: This study uses a true experimental research design conducted on white rats. Samples were taken by random sampling and divided into four groups, namely control group (KK) (n = 6), treatment group with a dose of 10% (P1) (n = 6), treatment group with a dose of 15% (P2) (n = 6) and treatment group with a dose of 20% (P3) ( n = 6). Results: The mean of wound’s length in KK=0.78 cm, P1=0.67 cm, P2=0.57 cm, and P3=0.15. Based on the Kruskal Wallis test, p value=0.000(α0.05), there is a significant difference in the wound healing process between the control and treatment groups. Discussion: Betel leaf contains active substances, namely flavonoids, alkaloids, saponins, tannins, and essential oils. The active substance causes the wound’s edges to close faster, so the wound heals faster.ABSTRAKPendahuluan : Luka sayatan adalah luka yang sengaja dibuat dengan sayatan bersih menggunakan benda tajam. Daun sirih merupakan bahan alami yang membantu proses penyembuhan luka, karena memiliki bahan aktif seperti saponin, tanin, flavonoid, minyak atsiri dan alkaloid. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak daun sirih terhadap proses penyembuhan luka sayatan pada tikus putih. Metode : Penelitian ini menggunakan rancangan penelitian true eksperimental yang dilakukan pada tikus putih. Sampel diambil secara random sampling dan dibagi menjadi empat kelompok yaitu kelompok kontrol (KK) (n = 6), kelompok perlakuan dengan dosis 10% (P1) (n = 6), kelompok perlakuan dengan dosis 15% ( P2) (n = 6) dan kelompok perlakuan dengan dosis 20% (P3) ( n = 6). Hasil : Hasil penelitian menunjukkan bahwa rerata panjang luka pada KK=0,78 cm, P1=0,67 cm, P2=0,57 cm, dan P3=0,15. Berdasarkan uji Kruskal Wallis didapatkan nilai p=0,000(α0,05), yang berarti terdapat perbedaan yang signifikan dalam proses penyembuhan luka antara kelompok kontrol dan perlakuan. Pembahasan : Daun sirih mengandung zat aktif yaitu flavonoid, alkaloid, saponin, tanin, dan minyak atsiri. Zat aktif tersebut menyebabkan tepi luka lebih cepat menutup, sehingga luka lebih cepat sembuh.